COMPARATIVE STUDY ON THE PHYTOCHEMICALS AND ANTIMICROBIAL POTENTIALS OF EXTRACTS OF Moringa oleifera and Telfaria occidentalis ON ANTIBIOTIC RESISTANT ORGANISMS - Musa Yakubu, Tula; Gabriel Galadima, Memi (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2017)
Resistance to antibiotics by etiologic microbial agents resulted in the quest for natural products with novel antimicrobial activity that will help to manage or combat the menace caused by resistant organisms. Therefore this study explores the phytochemicals of different extracts of Moringa oleifera and Telfaria occidentalis and their invitro biologic effect on antibiotic resistant organisms. The plants parts used for this study (M. oleifera leaves and seed and T. occidentalis leaves) were screened for phytochemical components from four solvents (ethanol, acetone, cold water and hot water). The results showed the presence of cardiac glycoside and polyphenols in all the extracts of M. oleifera seed and leaves respectively. Similarly, saponin was detected in all the extracts of T. occidentalis leaves and all the extracts of M. oleifera seed. Anthraquinone was not detected in the extracts of both plant parts. Other phytochemical components such as phlobatannins, alkaloids steroids and flavonoids were detected variably in both the plants parts extract. The antimicrobial activity of both plant parts were tested against multi-drug resistant Staphylococcus aureus, Salmonella typhi, Escherichia coli and Candida albicans at 100mg/ml concentration for all extracts. The tested organisms were resistant to cold and hot aqueous extracts of M. oleifera seed and also to cold aqueous extract of M. oleifera leaves. Also, all the tested organisms were not susceptible to hot aqueous extract of T. occidentalis leaves. However, the organisms were variably susceptible to ethanol and acetone extracts of M. oleifera with zones of inhibition which ranged from 12mm – 17mm for M. oleifera seed and 8 – 12mm for M. oleifera leaves. For T. occidentalis however, the cold aqueous extract exhibit higher (15 – 19mm) antimicrobial activity against the tested organisms in comparison to ethanol (10 – 16mm) and acetone (13 – 14mm) extracts. The results further revealed that the antimicrobial activities of leaves and seed of M. oleifera on all the isolates were not statistically different (P=0.333) and were not significantly different from the extracts of T. occidentalis leaves (P=0.645). Based on solvents used, the antimicrobial activity of ethanol and acetone extracts of all the plants parts were not statistically different (P=0.799), but were significantly higher than that of cold aqueous extracts of all the plants parts (P=0.007). However, the antimicrobial activity of cold aqueous extracts of T. occidentalis leaves on all the isolates was not significantly different from that of acetone extracts (P=0.109) and ethanol extracts (P=0.065) of all the plants parts. This result therefore showed that the leaves and seed of M. oleifera and T. occidentalis leaves if harnessed and exploited adequately may be sources of antimicrobial agent and a potential remedy for the treatment of infections caused by the organisms under study.